Analysis of proteins and potential bioactive peptides from tilapia (Oreochromis spp.) processing co-products using proteomic techniques coupled with BIOPEP database. (December 2015) - Huang, Bo-Bin; Lin, Hsin-Chieh; Chang, Yu-Wei
Highlights: Peptides with potential biological activities identified from tilapia proteins. Papain was suggested to produce potential ACE-inhibitory peptides by BIOPEP analysis. Tilapia collagen contains potential antiamnesic and antithrombotic activities. Abstract: Processing co-products from tilapia are abundant in proteins and can be great sources to produce potential bioactive peptides. The proteins from tilapia frame and skin were isolated by alkaline extraction and precipitation techniques with crude protein contents of 82.06% and 89.47% (w/w), respectively. A total of 7 tilapia proteins were identified by proteomic techniques and further analysed using BIOPEP database. Peptide cutter analysis with BIOPEP suggested that papain can release highest number of potential angiotensin converting enzyme (ACE)-inhibitory peptides from alpha actin, collagen alpha-1(I) chain-like isoformX2, collagen alpha-2(I) chain-like isoformX1 and myosin heavy chain. Bromelain, chymotrypsin C, ficain, pancreatic elastase, papain and proteinase K were the proteinases leading to the release of peptides with ACE-inhibitory, antithrombotic and antiamnesic activities from tilapia collagens. Myosin heavy chain was identified as a good precursor of antioxidant peptides. In silico results indicated protein isolates from tilapia co-products can represent high value-added products or ingredients.